Conversion to bioenergy crops alters the amount and age of microbially-respired soil carbon. (January 2019) - Szymanski, Laura M.; Sanford, Gregg R.; Heckman, Katherine A.; Jackson, Randall D.; Marín-Spiotta, Erika
Abstract: Bioenergy cropping systems have the potential to supply plant biomass as lignocellulosic feedstock for biofuels and bioproducts that will reduce reliance on fossil energy. Identifying the effects of alternative bioenergy cropping systems on soil carbon (C) is necessary to assess the sustainability of renewable fuels. We measured the response of soil organic carbon (SOC) pools to four bioenergy cropping systems using soils collected at the establishment of the field trials and after five years in two soils of contrasting texture: a fine-textured silt loam (Mollisol) in south central Wisconsin and a coarse-textured sandy loam (Alfisol) in southwestern Michigan, USA. Crop management followed region-specific practices with no till with the intention of reducing soil C losses from cultivation. Cropping systems included an annual monoculture (continuous corn), two perennial monocultures (switchgrass and hybrid poplar), and a perennial polyculture (restored native prairie). Using a 365-d laboratory soil incubation and a three-pool model, we estimated sizes and turnover times of SOC in surface (0–10 cm) and deeper soils (25–50 cm). After five years, all soils had less bioavailable C as measured by microbial respiration. To determine potential differences in soil C turnover under annual and perennial monocultures, we measured radiocarbon abundance ( 14 C) of bulk soils and respired CO2 under corn and switchgrass. Respired-CO2 was more depleted in 14 C over time, indicating preferential respiration of relatively "old C" after five years. Decreased microbial respiration rates after five years of bioenergy cropping systems offer the potential for the eventual reduction of soil C losses after conversion to no till. However, the 14 C-CO2 data suggest that previously-protected C pools may become depleted over time, especially with continued removal of plant inputs. Results show that conversion of conventional field-crop agriculture to bioenergy cropping systems may not provide belowground C benefits in the short term, as indicated by reductions in the size of the active pool. Reduced total soil respiration over the length of the study, as well as system-specific differences in soil respiration (monoculture annuals < monoculture perennial < polyculture perennials), suggest C loss may decline in perennial polyculture systems as they age. SOM pools responded differently to bioenergy crop management on soils with contrasting texture, highlighting the importance of geography in predicting belowground consequences of intensified agricultural production. Highlights: Soil microbial respiration rates decreased after five years of cropping. Active carbon pool (Ca ) dynamics were not affected by bioenergy biomass crop types. All systems lost carbon associated with the active C pool (Ca ) in surface soils. Microbes accessed different soil C pools after 5 years of cropping. Soil microbial respiration was greatest in diverse perennial plots.